The Technology of LEO Satellite Communication Systems Utilization for the Rapid Exchange of Data with the Low-altitude Spacecraft: Scientific Technological Equipment "Kontakt-MKA" On the Small Spacecraft "AIST-2". (2015) - Belokonov, Igor; Avariaskin, Denis; Davydov, Denis
Abstract: In this paper was analyzed thepossibility ofcommunication sessions withthe small spacecraftvia theGlobalstarsystem. Theduration of communicationsessions was estimated.It was made astochasticanalysis ofthe data transmission capabilitiesbetween the twospacecraftvia theGlobalstarsystem. The probability ofdata transmission between twospacecraft, depending on data volumeandworkload ofthe Globalstar system was estimated. The spaceexperiment on thesmall spacecraft "AIST-2" is planning to testthe results.